Ciri Khas Pedalangan Gaya Kerakyatan Subgaya Ngawonggo - Pulung Wicaksana Nugraha (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
This research entitled “Ciri Khas Pedalangan Gaya Kerakyatan Subgaya Ngawonggo” (Typical Characteristics of Folk Puppetry in the Ngawonggo Substyle) aims to identify the characteristics of folk puppetry in the Ngawonggo substyle. The approach used is qualitative analysis with descriptive methods through field data analysis. The research results show that the Ngawonggo substyle has its own characteristics. Firstly, the puppeteers of this substyle have descendants from the palace who have maintained the tradition of puppetry from generation to generation. Secondly, there is a standard Lakon consisting of seven series with the character Gatotkaca always playing a role in it. Thirdly, there is a Gatotkaca-Baladewa war scene before entering the line. This war scene uses udanegara or ethics in playing it.